ANALISIS SEA LEVEL VARIABILITY MENGGUNAKAN SATELIT SARAL ALTIKA DAN JASON - Hamidatul Aminah; Eko Yuli Handoko; Yuwono Yuwono (Kokoh, 2021)
Altimetry satellite technology is used to regulate sea level. Observations are carried out every year to study the dynamics of sea level in the world. Sea level anomalies (SLA) in each region have different values and vary greatly. The main cause that increases from sea level is the thermal increase that increases from the mass of water from melting ice and glaciers on the surface of the earth. Therefore, this research aims to calculate the SLA from the SARAL / AltiKa satellite data and Jason's satellite series to study the variability of sea level in Indonesia's western sea, namely: the Java Sea, Karimata Strait and the South China Sea. From the research conducted, sea level rise obtained using SARAL / AltiKa satellite data in the range of -10 mm to 8 mm at a rate of decline of 0,459 mm / year. Meanwhile, Jason's series satellite data produces sea surface variations of around -2 mm to 11 mm at a rate of decline of 0,817 mm / year. From these two satellite observations, sea level decreases occur in the Java Sea, while in the Karimata Strait and parts of the South China Sea increasing sea level rise. In addition, this study uses research analysis to study the association of SLA data from SARAL / AltiKa and Jason satellite observations. The results of comparative analysis are very strong and in line with the estimated coefficient value of 0,9332.Keywords: Altimetri, Jason, Perairan Indonesia, SARAL/AltiKa, Sea Level Anomaly, Trend